2008
DOI: 10.1017/s0007114507877658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blueberry feeding on plasma lipids in pigs

Abstract: Two feeding trials were conducted with pigs to determine the effects of blueberry supplementation on plasma lipid levels and other indices of cardiovascular benefit. In the first trial, where basal diets contained a high level of plant-based components (70 % soya, oats and barley), supplementation with 1, 2 and 4 % blueberries resulted in a decrease in total, LDL-and HDL-cholesterol. The greatest reduction was observed in the 2 % blueberry-fed pigs, where total, LDL-and HDL-cholesterol were reduced 11·7, 15·1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
(51 reference statements)
2
40
0
Order By: Relevance
“…Kalt et al also showed that pigs fed diets supplemented with 1 , 2 , and 4 freeze-dried blueberry leaf powder showed a decrease in total, LDL-, and HDLcholesterol levels, although no dose response was evident 24 . The antiatherosclerotic effect of dietary freezedried blueberry leaf powder has been shown at the 1 dietary level in apolipoprotein E-deficient mice, although this effect was independent of an altered serum lipid profile or total antioxidant capacity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Kalt et al also showed that pigs fed diets supplemented with 1 , 2 , and 4 freeze-dried blueberry leaf powder showed a decrease in total, LDL-, and HDLcholesterol levels, although no dose response was evident 24 . The antiatherosclerotic effect of dietary freezedried blueberry leaf powder has been shown at the 1 dietary level in apolipoprotein E-deficient mice, although this effect was independent of an altered serum lipid profile or total antioxidant capacity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with obese mice treated with a high-anthocyanin beverage or diet corroborate our findings 10,21 . Polyphenols have been found to reduce the total cholesterol of animals fed atherogenic diets 5,12 and even healthy diets 4,22 . Another study found that HFJ2 and HFJ4 diets were capable of increasing HDL-cholesterol 6 .…”
Section: Discussionmentioning
confidence: 99%
“…High-polyphenol and high-fiber diets are capable of reducing total cholesterol and Low Density Lipoprotein-cholesterol (LDL-cholesterol) 4,12 , suggesting that both substances may act synergistically on the regulation of blood lipids. Moreover, diets supplemented with 1% or 2% freeze-dried jaboticaba peel improved the antioxidant capacity of rat plasma, indicating the potential of freeze-dried jaboticaba peel compounds to attenuate oxidative stress 13 and related damages 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Pigs fed with a diet containing cereals/grains supplemented with fiber source and 1.5% blueberries resulted in reduced total cholesterol (Kalt et al, 2008). Thus, it is possible that consumption of foods containing a combination of phenolic compounds and fibers provide improvements of glycemic and lipids control in vivo.…”
Section: Troductionmentioning
confidence: 99%